Does inversion affect boundary extension for briefly-presented views?. Issue 3 (15th March 2016) - Beighley, Steven; Intraub, Helene
ABSTRACT: Inverting scenes interferes with visual perception and memory on many tasks. Might scene inversion eliminate boundary extension (BE) for briefly-presented photographs? In Experiment 1, an upright or inverted photograph (133, 258, or 383 ms) was followed by a 258 ms masked interval and a test photograph showing the identical view. Test photographs were rated as "same", "closer", or "farther away" (5-point scale). BE was just as great for inverted as upright views at the 133 and 383 ms durations, but surprisingly was greater for inverted views at the 258 ms duration. In Experiment 2, 258-ms views yielded greater BE when the study photographs were always tested in the opposite orientation, indicating that the difference in BE was related to encoding. Results suggest that scene construction beyond the view boundaries occurs rapidly and is not impeded by scene inversion, but that changes in the relative quality of visual details available for upright and inverted views may sometimes yield increased BE for inverted scenes.